1985
DOI: 10.1111/j.1528-1157.1985.tb05409.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes Toward Epilepsy in Italy: Results of a Survey and Comparison with U.S.A. and West German Data

Abstract: In May 1983, the Italian Institute of Public Opinion DOXA ran, for the Italian League Against Epilepsy, a survey to evaluate public attitudes toward epilepsy in Italy. Eight questions were addressed to a sample of 1,043 adults. Twenty-seven percent did not know what epilepsy was. The least knowledge was observed among elderly people, in the southern regions and the islands, in villages more than in cities, and, in particular, among the poorest social classes. Sixty-one percent had known someone who had epileps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
2
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 5 publications
7
86
2
2
Order By: Relevance
“…Table 4 shows the differences obtained in the answers about familiarity with the disease in many countries. It is observed that, although many people have already seen a seizure and know someone who suffers from the disease, the non-college population of Caxias do Sul is one of the least informed populations about the disease, with proportions similar to people in Hong Kong 10 and Italy 3 . Besides that, when we compare this group (G1) to the general population sample of Campinas, Brazil, obtained in the 90's, no improvement has been observed in the level of familiarity with the disease after more than a decade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 shows the differences obtained in the answers about familiarity with the disease in many countries. It is observed that, although many people have already seen a seizure and know someone who suffers from the disease, the non-college population of Caxias do Sul is one of the least informed populations about the disease, with proportions similar to people in Hong Kong 10 and Italy 3 . Besides that, when we compare this group (G1) to the general population sample of Campinas, Brazil, obtained in the 90's, no improvement has been observed in the level of familiarity with the disease after more than a decade.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires that evaluate the perception of epilepsy in many different social segments have been used by a great number of authors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Although many limitations have been observed such as understanding the questions, diffi culty in achieving the right answer since there is a broad range of epilepsies, the tendency is to not expose negative positions on the subject and the non-validation of the instrument 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The main problem with this questionnaire is that it treats epilepsy as an entity, while much depends on the severity of the epilepsy, whether you do or not object to a marriage in the family and again much depends on the type of epilepsy and the type of work whether you do or do not hire a person with epilepsy.Some of these aspects have been discussed in the literature 3 . Despite these limitations, this approach has been employed in several countries [1][2][3][4][5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-seven percent of Chinese 5 , 42% of Taiwanese 7 , 36% of Finns 3 , 40% of southern Italians 4 and 41% of Americans 1 were ignorant of the causes of epilepsy. Thirty and 32% of Groups II and III (pre-university and university students) had similar levels of knowledge to the general population in studies from other countries.…”
mentioning
confidence: 99%
“…Negative public attitude toward epilepsy is a common phenomenon all over the world (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), and is the major factor causing serious social discrimination against people with epilepsy. In general, those with epilepsy have considerable limitations in their interaction with and adaptation to their surroundings; some of them find social attitudes toward them more devastating than the disorder itself (11).…”
Section: Introductionmentioning
confidence: 99%